Incidencia del crecimiento económico en el desempleo juvenil de ecuador periodo 2010-2019 - Maita Robles, Maria Cristina (2022)
Unemployment in young people is a problem that has persisted for many years, causing economic and social problems. Worldwide, 13.6% of them are unemployed (OIT, 2020). For this reason, this research aims to analyze the incidence of economic growth in youth unemployment and other possible causes of this phenomenon in Ecuador, from the period 2010 to 2019. The information was compiled from the databases of the Central Bank of Ecuador [BCE] (2020), the National Survey of Employment and Underemployment (ENENDU), published by the National Statistics and Census Institute [INEC] (2020), and from the Directory of Companies [DIIE] (2020). Therefore, a Generalized Least Squares (GLS) model, Pedroni's (1999) cointegration test, and Dimietry and Hurlin's (2012) causality test were estimated. Allowing in this way obtain results that: economic growth has a positive relationship with youth unemployment; schooling presents a negative relationship with youth unemployment; and it was determined that there is a long-term relationship between economic growth, schooling, and youth unemployment. In addition, it was found that there is a bidirectional relationship, which goes from youth unemployment to economic growth, and consequently, the policy implications should focus on promoting the development of new productive activities and adding value to production through the incorporation of technology and knowledge in production processes; also, it is suggested to update teaching methods that allow students to better develop their skills.